THE CONCEPT OF LOVE AND MARRIAGE IN ZORA NEALE HURSTON'S THEIR EYES WERE WATCHING GOD - Asst. Lecturer Farah Mahmood Abbas (College of Education for Women, 2019)
Zora Neale Hurston's (1891-1960) is an outstanding African American novelist, playwright, autobiographer and essayists. Her work is considered as an important part of the African American and Harlem Literature.**** It represents a milestone and a keystone in the African-American literary canon because it breaks from the style of the previous works and makes a beginning of a new style. Hurston shifts from the black works that stick to racial themes and sheds the light on new aspects and themes in blacks' life especially on feminist themes. Her exceptional fame culminates in her novel Their Eyes Were Watching God (1937). 1 Their Eyes Were Watching God examines with a great deal of artistry the struggle of a black woman named Janie Crawford to escape the fetters of the traditional concept about love and marriage and the narrow social restrictions of her class and sex. She neglects others' judgment on her and is brave enough to strive for her dream.2 The paper concentrates on this novel to show the concept of love and marriage through the story of Janie's Crawford, the novel's protagonist. In Janie's plight towards liberty and recognition, love and happiness, Hurston reflects the colored women's thrives and experiences in the American black society. Janie, who has the concept that marriage must involve love and happiness, goes for a search of unconditional and fulfilling love which she finally finds with her third husband Tea Cake, but only after she has passed through the wasteland of being a possession before entering the pear tree garden of her actualized dreams of love and happiness.